Microbiome Composition and Its Impact on the Development of Allergic Diseases - Peroni, Diego G.; Nuzzi, Giulia; Trambusti, Irene; Di Cicco, Maria Elisa; Comberiati, Pasquale (Frontiers in Immunology, 2020)
The microbiome evolves from the first moments of life and gradually diversifies concomitantly with the physiological development of the host individual. Microbiome composition is influenced by several environmental factors, including the mode of delivery, breastfeeding, gestational age, antibiotics use, and diet. The resident microbial communities in the human gut and in other organs have been shown to modulate the host growth and functions for nutrition and immunity. Increasing evidence shows that early life interactions between the host-microbiome and the immune cells play a pivotal role in the development of the immune system. Therefore, the process of early colonization by a “healthy” microbiome is emerging as a key determinant of life-long health. In stark contrast, the perturbation of such a process, which results in changes in the composition and metabolic activities of the host microbiome, has been associated with greater susceptibility to non-communicable diseases later in life, including allergic diseases. In this review, we outline recent findings regarding the relationship between the gut microbiome and host immune system development and address how the modulation of the human microbiome in different body districts could be a potential strategy for the prevention and treatment of allergic diseases.